The effect of economic policies on urban transport patterns: A review of motorcycle usage for urban mobility in Nigeria - Gbagir Kwaghgba; Tyozenda Aondofa (Journal of Sustainable Development of Transport and Logistics)
Purpose: This review examines the effects of Nigeria's economic policies, particularly the removal of fuel subsidies, on urban transport patterns, focusing on the increased use of motorcycles for daily commuting. Methodology: A comprehensive literature review was conducted, analyzing studies on motorcycle usage in urban areas of Nigeria and other developing countries and the impact of economic policies on transportation choices. Results: The study finds that removing fuel subsidies has significantly increased motorcycle usage in Nigerian cities, particularly among low-income earners. This shift has resulted in changes to traffic flow, increased road safety concerns, and environmental challenges due to motorcycle emissions. Theoretical contribution: The paper contributes to the understanding of how economic policies can rapidly transform urban mobility patterns in developing countries, highlighting the complex interplay between affordability, safety, and environmental sustainability in transportation choices. Practical implications: The review identifies several policy interventions, including enforcing safety regulations, creating dedicated motorcycle lanes, and improving traffic management systems. It also emphasizes the need for holistic transport policies that balance economic realities with safety and sustainability concerns.